Active thermal NDT: problems and solutions; Proceedings of SPIE; Vol. 9861 : Thermosense: Thermal Infrared Applications XXXVIII - Vavilov V. P. Vladimir Platonovich (Nondestructive Testing and Composites, 2016)
Title screen